2019
DOI: 10.1186/s13033-019-0306-7
|View full text |Cite
|
Sign up to set email alerts
|

Key attributes of integrated community-based youth service hubs for mental health: a scoping review

Abstract: Background Community-based, integrated youth service hubs have the potential to address some of the longstanding issues with mental health services for youth, including problems with access and system fragmentation. Better understanding of these approaches, particularly efforts to create a single point of entry to comprehensive, evidence-based services through youth service hubs, is needed to help guide future implementation and evaluation. This scoping review identifies the key principles and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
149
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(157 citation statements)
references
References 96 publications
6
149
1
1
Order By: Relevance
“…Practical experiences and literature indicate that these young people have a hard time accessing and remaining in regular outpatient mental healthcare 4 33 38. Several reasons for treatment disengagement in adolescents have been suggested, such as fragmented healthcare system,50 treatment discontinuity51 52 and difficulty to trust services 53. According the Youth Flexible ACT model description4 young people are eligible for Youth Flexible ACT care if:…”
Section: Methods and Analysismentioning
confidence: 99%
“…Practical experiences and literature indicate that these young people have a hard time accessing and remaining in regular outpatient mental healthcare 4 33 38. Several reasons for treatment disengagement in adolescents have been suggested, such as fragmented healthcare system,50 treatment discontinuity51 52 and difficulty to trust services 53. According the Youth Flexible ACT model description4 young people are eligible for Youth Flexible ACT care if:…”
Section: Methods and Analysismentioning
confidence: 99%
“…Community-based integrated care system and implementation Based on the above results, further research is needed to reveal how host societies can enrich opportunities for immigrants' mental health and improve access to social networks for support. There is an international movement toward developing a community-based integrated mental health service, in which mental health professionals and policy makers work together [56][57][58]. Recent review articles have suggested that an integrated care system for young people was effective for the prevention of mental illness and for early intervention [42].…”
Section: Limitationsmentioning
confidence: 99%
“…In addition, researchers have argued that the analysis of social connections within networks is the most valuable way to reveal the smaller scale interactions that influence broad scale patterns [4]. Integrated youth service (IYS) is a collaborative model that brings organisations together to provide holistic care that often includes mental health, substance use and addictions, primary care (including sexual health) and other social services [5][6][7][8][9]. Frayme is an international knowledge translation (KT) network designed to support the uptake and scaling of IYS [5,10].…”
Section: Introductionmentioning
confidence: 99%